A NOTION AND STATUS OF INDEPENDENT REGULATORY AGENCIES IN THE REPUBLIC OF MACEDONIA - Mustafi, Muhamed; Saliu, Argëtim (International Scientific Journal Vision, 2018)
The nineteenth and twentieth century determined a special connection and interdependence between political and economic branches , which set the right platform for pre-sentation of the bodies or regulatory authorities. Macedonia was not overlooked by this connected determinism and inter-dependent. The formation of regulatory bodies by the Assem-bly in more diverse sectors in Macedonia began in 2002. The regulatory bodies have the status of legal entity by registration in court and their work is public. The role of the market, politics / government and civil so-ciety as a regulator with economic and political mechanisms that operate in democratic societies with market economies is, in fact, an appropriate balance of their roles as regulators of public affairs.